Syringohydromyelia in Dogs: The Genomic Component Underlying a Complex Neurological Disease - Sandra Andrino; Valentina Lorenzo; Susana Dunner; Elisabeth Contreras; Javier Cañón; Natalia Sevane (Animals, 2022)
Syringohydromyelia (SHM) is a neurological disorder characterized by the appearance of fluid-containing cavities within the spinal cord. Although SHM is thought to be under multigenic control, the molecular basis of this disease remains poorly defined. A genome-wide association study (GWAS) was carried out comparing the whole genome sequences (WGS) from 12 dogs with SHM and 2 panels of 26 dogs (either older than 5 years and showing the absence of SHM or belonging to breeds not susceptible to SHM) to identify candidate genes associated with the development of SHM. Seven candidate genes were identified. Of these, five genes were determined to be involved in bone development (PLXNA2, HHAT, MBOAT2, ITGAV) and calcium homeostasis (HPCAL1). Although further validation is needed at the transcript level, it is worth highlighting the association of a possible pathogenic variant which generated a new intronic branch-site sequence in PLXNA2 (T/C, CFA7:7043294). Considering previous studies in dogs that show SHM related to craniocervical junction (CCJ) malformations, these genes can be considered good candidates for the development of this disease. This report dissects the genomic component of SHM in dogs, which paves the way for further research on this complex disease found both in canine and human species.